PELAKSANAAN KEGIATAN PRAMUKA DI SD NEGERI 164 KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Sarah Meilinda Alfarisy; Aswandi Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Scouting is one of the compulsory extracurricular activities. This is in accordance with the regulations of the Minister of Education and Culture of the Republic of Indonesia Number 81A Year 2013 On Implementation of Curriculum , explained that the extracurricular activities is one of the operational tools ( supplements and complements ) curriculum .Scouting is one of the extracurricular activities that could form the self and personality of students who become knowledgeable Indonesian human knowledge and can apply the high - noble noble values of the nation. This study aims to investigate the implementation extracurricular scouts of SD Negeri 164 in Pekanbaru . The method in this research is qualitative descriptive . The theory underlying this study is a component of the implementation of learning . The data collection techniques used in this research is interview , observation and documentation. Implementation of the scouts in terms of the various components, namely : (a) Interest , (b) materials , (c) Methods , (d) Media (e) Assessment. Results obtained from the data : 1) the purpose of the implementation of the scouts from the general and specific objectives .2) The material taught during a semester that lasts scout ceremonies material , material code , material and semaphore and rigging material. 3) methods are often used in learning scout is a lecture and practice . 4) The media used consisted of two kinds, namely two or three-dimensional media and media projectors.Keywords : Implementation , Extracurricular , Scouts